The Impact of Exchange Rate Movements on Trade Balance between Vietnam and Japan: J Curve Effect Test - Nhung, Nguyen Cam; Anh, Bui Tu; Hue, Le Thi; Huyen, Nguyen Thi Cam (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 2, 2018)
This study clarifies the impact of the fluctuation of the VND/USD and VND/JPY exchange rates on the trade balance between Vietnam and Japan through testing the J-curve effect by using a vector autoregressive (VAR) model, Impulse Response Function (IRF), stationary test, Granger test and variance decomposition analysis. There are 5 variables including oil price (POIL), Gross Domestic Product (GDP), Consumer price index (CPI), Trade balance/Capital account (CA), Nominal exchange rate (NER) based on 67 observations from 2001Q1 to 2017Q3. The highlight of this study compared with previous studies is that we not only evaluate the effect of the exchange rate movements towards the total trade balance between Vietnam and Japan but also investigate how the fluctuations of exchange rate affect the trade balance in each commodity group; therefore, we suggest more essence evaluation and policy implications for these sectors. The results show that the depreciation or the devaluation of VND will improve the trade balance of group 84 (Machinery, mechanical appliances, nuclear reactors, boilers) and group 94 (Furniture) in both the exchange rate VND/USD and VND/JPY, and group 27 (Mineral fuels, mineral oils and products of their distillation) and group 85 (Electrical machinery and equipment and parts thereof) in the VND/USD exchange rate. Besides, in total products and group 27, the VND/JPY exchange rate impacts on the trade balance in J-curve effect.